ROLE OF PQRST IN DEVELOPING READING SKILL - EFFRINA YURICKI (JETA (Journal of English Teaching and Applied Linguistic), 2024)
PQRST technique is used to improve students’ reading skill at the eighth-grade students of SMP Negeri 2 Bandar Mataram. In this research, the writer took Classroom Action Research (CAR). This reasearch conducted 31 students including 15 male and 16 female students. The writer devided into two classes and included four stages such as; planning, action, observation adn refletion. In a pre-cycle, the writer assess identifying initial reading, challages, guiding targeted intructional strategies. For collecting data, writer took interviews, field notes, observation checklists and reading test showed clear improvements. Based on the data, the writer got the average learnig activity score rose from 3.42 (“fair”) in Cycle 1 to 3.95 (“fair to good”) in Cycle 2. Reading scores also improved significantly: the pre-cycle average of 53.19 (9.67% meeting the Minimum Mastery Criterion, MMC) increased to 71.61 in Cycle 2, with 61.29% of students achieving or surpassing the MMC. In conclusion, the PQRST technique effectively enhanced students’ engagement and reading comprehension, though further refinements may be needed to reach the full mastery criterion of 75% for the class.